Biodistribution and toxicity of spherical aluminum oxide nanoparticles. Issue 3 (5th October 2015) - Park, Eun‐Jung; Lee, Gwang‐Hee; Yoon, Cheolho; Jeong, Uiseok; Kim, Younghun; Cho, Myung‐Haing; Kim, Dong‐Wan
Abstract: With the rapid development of the nano‐industry, concerns about their potential adverse health effects have been raised. Thus, ranking accurately their toxicity and prioritizing for in vivo testing through in vitro toxicity test is needed. In this study, we used three types of synthesized aluminum oxide nanoparticles (AlONPs): γ‐aluminum oxide hydroxide nanoparticles (γ‐AlOHNPs), γ‐ and α‐AlONPs. All three AlONPs were spherical, and the surface area was the greatest for γ‐AlONPs, followed by the α‐AlONPs and γ‐AlOHNPs. In mice, γ‐AlOHNPs accumulated the most 24 h after a single oral dose. Additionally, the decreased number of white blood cells (WBC), the increased ratio of neutrophils and the enhanced secretion of interleukin (IL)‐8 were observed in the blood of mice dosed with γ‐AlOHNPs (10 mg kg −1 ). We also compared their toxicity using four different in vitro test methods using six cell lines, which were derived from their potential target organs, BEAS‐2B (lung), Chang (liver), HACAT (skin), H9C2 (heart), T98G (brain) and HEK‐293 (kidney). The results showed γ‐AlOHNPs induced the greatest toxicity. Moreover, separation of particles was observed in a transmission electron microscope (TEM) image of cells treated with γ‐AlOHNPs, but not γ‐AlONPs or α‐AlONPs. In conclusion, our results suggest that the accumulation and toxicity of AlONPs are stronger in γ‐AlOHNPs compared with γ‐AlONPs and α‐AlONPs owing their low stability within biological system, and the presence of hydroxyl group may be an important factor in determining the distribution and toxicity of spherical AlONPs. Copyright © 2015 John Wiley & Sons, Ltd. Abstract : In this study, we used three‐types of synthesized aluminum oxide nanoparticles (AlONPs): γ‐aluminum oxide hydroxide nanoparticles (γ‐AlOHNPs), γ‐ and α‐AlONPs. All three AlONPs were spherical, and the surface area was the greatest for γ‐AlONPs, followed by α‐AlONPs and γ‐AlOHNPs. In mice, γ‐AlOHNPs accumulated the most 24 h after a single oral dose. Additionally, the decreased number of WBC, the increased ratio of neutrophils and the enhanced secretion of IL‐8 were observed in the blood of mice dosed with γ‐AlOHNPs (10 mg kg −1 ). In the in vitro test using six cell lines, BEAS‐2B, Chang, HACAT, H9C2, T98G and HEK‐293, which were derived from their potential target organs, γ‐AlOHNPs induced the greatest toxicity. Moreover, separation of particles was observed only in the TEM image of cells treated with γ‐AlOHNPs.